Identifikasi Efek Latihan Intensitas Tinggi Terhadap Peningkatan Kapasitas Aerobik Pada Mahasiswa - Hernani, Aldina; Jalal, Abdul; Firdhani, Amelia Chusna; Adam, Brian; Khayati, Eka Nur; Candella, Gheiyanova; Farhani, Muhammad Anggaraksa; Hidayatullah, Muhammad Bintang; Baihaqi Elsyam, Muhammad Faisal; Mahendra, Raditya Duta; Afifah, Safrilla Kurniatul; Nur Khomariyah, Siti Afifatul; Sofiyulloh, Tamara Devi (Jurnal Kepelatihan Olahraga, 2024)
AbstractMaintaining health and physical fitness for today's students is a need that needs attention. In this study, researchers wanted to increase aerobic capacity in a group of students. This research involved 10 samples who were actively participating students. In this study they were 19-20 years old, with that age range they would take part in this exercise. This research uses a one group pre-post design. This research shows that group A's Tabata training is much better than group B, because in the paired test the Vo2Max results for group A and group B are different. Based on the results of data analysis, descriptions, testing research results, and discussion, it can be concluded that HIIT training using the Tabata method can increase aerobic capacity in students.